The economy of Africa - Hazlewood, Arthur (London : Oxford University Press, 1961)
This aims to make accessible to African leaders and citizens knowledge relevant to political, social and economic changes going on in Africa.
Includes index.
kjo 17/01/2019
Loans
Keywords: Economy; Economic development; Economy conditions; Africa